PERBAIKAN PENDAPATAN PETERNAK SAPI PENGGEMUKAN MELALUI PEMANFAATAN LAMTORO TARAMBA DI KECAMATAN UNTER IWIS, KABUPATEN SUMBAWA, NTB - Hermansyah, Hermansyah; Fachry, Anwar; Nugroho, Prasetyo; Dilaga, Syamsul Hidayat (Jurnal Pepadu, 2024)
This community service activity in addition to aiming to increase the income of farmers by utilizing Lamtoro Taramba as feed for fattening cattle is also aimed at saving the environment from the influence of erosion due to massive land deforestation that has occurred recently, including in Unter Iwis District, Sumbawa Regency. Apart from receiving short training on seed selection procedures, seeding patterns, harvesting and techniques for using Lamtoro taramba, farmers are also given input on economic calculations regarding the results of fattening cattle using Lamtoro taramba compared to using other feed crops.. The results of the service show that lamtoro taramba is trusted by breeders as a plant that has many benefits in the process of fattening cattle, and is no longer considered a pest that destroys land and the environment. The consolidation of breeders into groups makes it easier for the Sumbawa District Government to provide guidance on feed and the environment.